2013
DOI: 10.1016/j.freeradbiomed.2012.10.553
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and IL-13 employ discrete signaling pathways for target gene expression in alternatively activated monocytes/macrophages

Abstract: Monocytes/macrophages are innate immune cells that play a crucial role in the resolution of inflammation. In presence of Th2 cytokines interleukin-4 (IL-4) and interleukin-13 (IL-13), they display an anti-inflammatory profile and this activation pathway is known as alternative activation. In this study we compare and differentiate pathways mediated by IL-4 and IL-13 activation of human monocytes/macrophage. Here we report differential regulation of IL-4 and IL-13 signaling in monocytes/macrophages starting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
167
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(190 citation statements)
references
References 56 publications
13
167
0
3
Order By: Relevance
“…Interestingly, only a subset of IL-4-stimulated genes, most prominently ALOX15, is inhibited upon AMPK activation. It is known that, in addition to STAT6, STAT3 is involved in the regulation of ALOX15 in IL-4-treated human monocytes (22). Our data corroborate a role of STAT3 in regulating ALOX15 in response to IL-4, and we suggest that AMPK attenuates STAT3-dependent gene expression by preventing STAT3 association with upstream Jak1 tyrosine kinase, its tyrosine and serine phosphorylation, and nuclear translocation upon IL-4-treatment.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, only a subset of IL-4-stimulated genes, most prominently ALOX15, is inhibited upon AMPK activation. It is known that, in addition to STAT6, STAT3 is involved in the regulation of ALOX15 in IL-4-treated human monocytes (22). Our data corroborate a role of STAT3 in regulating ALOX15 in response to IL-4, and we suggest that AMPK attenuates STAT3-dependent gene expression by preventing STAT3 association with upstream Jak1 tyrosine kinase, its tyrosine and serine phosphorylation, and nuclear translocation upon IL-4-treatment.…”
Section: Discussionsupporting
confidence: 85%
“…To question the involvement of STATs in AMPK-dependent ALOX15 suppression, we analyzed tyrosine phosphorylation and nuclear translocation of STAT3 and STAT6 as signs of their activation in IL-4-treated cells in the presence of AICAR or phenformin. Furthermore, we analyzed phosphorylation of Jak1 kinase, which was reported to phosphorylate STAT3 and STAT6 in IL-4-stimulated monocytes (22). IL-4 elicited robust phosphorylations of Jak1, STAT3, and STAT6 within 15 min, which returned to baseline after 3 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On d 3, fluorescence intensity was strongest in the peritoneal area of the M(IL-4)-treated mice ( Figure 4A), a pattern that was similar to d -2 just mechanistic studies: would M(IL-4)s suppress colitis in a manner equivalent to that observed with M(IL-4 + IL-13)s, and would cryopreserved M(IL-4)s retain their ability to inhibit colitis. It is generally accepted that IL-4 is the key cytokine in the alternative activation of macrophages and that IL-13 complements or enhances the differentiation of the AAM via STAT3 and STAT6 signaling (27,28). Assessment of canonical markers of mouse and human AAMs revealed almost identical responses to IL-4 and IL-4 + IL-13 (IL-13 alone was a less potent stimulus of an AAM phenotype), a finding in accordance with data showing that bone marrow-derived macrophages and human monocytes were more Indeed, we, and others, have shown that adoptive transfer of AAMs retrieved from mice or differentiated in vitro from bone marrow precursors or peritoneal macrophages can suppress colitis (14)(15)(16)(17)(18)(19)).…”
Section: Transferred M(il-4)s Localize To the Colon During Dnbs Colitismentioning
confidence: 99%
“…or 'alternatively activated' macrophage, results from stimulation of Th2 cytokines interleukin (IL)-4 and IL3, are associated with tissue repair, wound healing and fibrosis (Bhattacharjee et al, 2013). Meanwhile, anti-inflammatory M2c macrophages induced by IL-10, release anti-inflammatory cytokines to deactivate the M1 phenotype and promote the proliferation of non-myeloid cells (Sica and Mantovani, 2012).…”
Section: Discussionmentioning
confidence: 99%